(untitled) (Foro de Educacion, 2017)
In order to contribute to rethink the teaching-learning processes related to higher education in dramatic art, the present text proposes three lines of reflection and action: first, the claim that theatrical production and interdisciplinarity are practices which encourage new ways of knowing, being and doing; second, the enhancement of educational and artistic tasks applied to the inherent complexity of training and professionalization in theatre arts; finally, the need to articulate an integrated educational project whose «methods» and paths should not be performed regardless the contributions of cooperative work and action research, which are due to all of those who in one way or another, as teachers and / or students, are involved in the transition between training and artistic work, and vice versa. In this paper, emerging from a systematic analysis of some experiences of theatrical production developed in a school of dramatic art, we propose to consider the processes of theatrical production in the light of what is known as integrated curriculum, based on the projects method and oriented to enhance the educational and civic dimension that any process should have in order to define, develop and achieve its goals. We conclude by offering some theoretical and methodological clues for the necessary transformation of theatrical production into a meaningful educational experience.